Troubleshooting of filamentous bulking using biofilm reactors - Matos, M. (2010)
The present work aims to evaluate filamentous bulking control in systems combining suspended biomass with biofilm growth. For this study, four sequencing batch reactors (SBR)fed with an easy biodegradable substrate (acetate) were operated without (SBR1) and with support for biofilm growth [5 % (SBR2), 10 % (SBR3) and 20 % (SBR4) of the reactor volume]. The results demonstrated an overabundance of a filamentous fungi-like microorganism in the SBR operating just with suspended biomass. The incorporation of an optimized amount of support for biofilm growth (10 % and 20 %) seemed to suppress the overgrowth of this filamentous microorganism probably due to the combined effect of a decreased biomass loading rate and the physical cut or breakdown of filaments induced by particle-to-particle collisions. Besides the observed differences in terms of the filamentous fungi-like microorganism, the incorporation of a support material for biofilm growth was also found to induce increasing differences in the bacterial community structure as the concentration of support increased in the SBR.